Antibiotics Prescribing Pattern of Outpatients in a Tertiary Level Hospital in Nepal - Sapkota, Kalyan; Pokharel, Deviram; Basel, Shailesh; Dhakal, Bijaya (Journal of College of Medical Sciences-Nepal, 2023)
Introduction. Antibiotics are most abundantly used drugs of major global concern for rapid ongoing emergence of resistant strains, increase overall cost of treatment and impact on national economy. Optimized use of antibiotic on the basis of proper diagnosis, prescriber’s attention about the problem and antimicrobial stewardship programs may become a way to rationalize the use.Methods. This is a cross-sectional descriptive study done in patients visiting to various OPD of tertiary referral hospital. Prescriptions were randomly selected and Antibiotics utilization was assessed by WHO prescribing Indicator form. Prescribed drugs were checked for adherence to guidelines and essential medicine list.Results. Among 731 sampled prescriptions, 384 (52.53%) were found with at least one antibiotic; 214 prescriptions (55.72%) were of female patients. Mean age was 37.71 years with SD 25.01. Highest numbers of patients (21.09%) belong to the 15-29 age group.  Highest number of patients 158 (41.15%) treated with antibiotics were seen in patient attending Medicine department, 30 antibiotics were prescribed for 577 times. Amoxicillin-Clavulanate 70 (12.13%) was the most frequently prescribed followed by Azithromycin and Metronidazole with frequency of 39 (6.76%). Drug availability is 50.36%, in the facility and only 2.4 % of drugs were prescribed in generic.Conclusions. More than half of the patients were prescribed with antibiotics and all antibiotics were prescribed empirically. Newer generation antibiotics with broad spectrum efficacy were used in remarkable frequency. This study provides evidence for antibiotic stewardship, drug use review and establishment of institutional guidelines.